2022
DOI: 10.1371/journal.pone.0271002
|View full text |Cite
|
Sign up to set email alerts
|

In silico approaches for drug repurposing in oncology: Protocol for a scoping review of existing evidence

Abstract: Drug repurposing has been applied in the biomedical field to optimize the use of existing drugs, leading to a more efficient allocation of research resources. In oncology, this approach is particularly interesting, considering the high cost related to the discovery of new drugs with therapeutic potential. Computational methods have been applied to predict associations between drugs and their targets. However, drug repurposing has not always been promising and its efficiency has yet to be proven. Therefore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…In silico approaches have proven to be significant in identifying novel drug candidates and repurposing existing drugs [ 12 , 18 , 19 ]. These studies have also been instrumental in shedding light on the likely mechanisms of action of single herbal drugs [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In silico approaches have proven to be significant in identifying novel drug candidates and repurposing existing drugs [ 12 , 18 , 19 ]. These studies have also been instrumental in shedding light on the likely mechanisms of action of single herbal drugs [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This scoping review protocol was developed according to the framework proposed by Arksey and O’Malley [ 10 ] and complies with the recommendations of the JBI for elaborating scoping reviews [ 11 ]. A similar study from Brazil on in silico approaches in drug repurposing served as a guide in formulating this scoping review protocol [ 12 ]. This protocol has been registered with Open Science Framework [ 13 ] and is reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guideline [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The cost of securing new medication has more than doubled in ten years [31], and new compounds may take 10-15 years to become available to the public [30]. Aside from being time-consuming and costly, drug development in oncology maintains a low success rate, with under 5% of tested drugs reaching the pharmacy shelves and the average patient [30,32,33]. One of the challenges behind this process is the difficulty in the translation of research from the laboratory to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This scoping review followed the methodological framework proposed by Arksey and O’Malley (2005) and complies with the recommendations of the Joanna Briggs Institute for elaborating scoping reviews ( Peters et al, 2015 ). The protocol has been previously published ( Cavalcante et al, 2022 ) and registered on the Open Science Framework ( https://osf.io/yx7kp ). Additionally, this review is reported following the PRISMA extension for scoping reviews ( Supplementary File S1 ) ( Moher et al, 2015 ; Page et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The electronic search strategies were conducted on 22 March 2022. Details regarding the search strategies employed in each database were previously published ( Cavalcante et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%